Characteristics of changes in the psychophysiological status of water transport workers in the condition of fatigue - Chernenko, E. V. (Journal of Education, Health and Sport, 2017)
The professional activity of water transport workers proceeds under conditions of a high degree of exposure to the body of a complex of adverse factors and mental stress. Of particular importance in these conditions is the observation of the functional state of a person, emotional comfort and prevention of fatigue. Organizational measures that are widely used at onshore enterprises, such as vnutrismenny rest, shortened working shift and week, additional leave - in the ship's conditions make little sense and only limited work experience and earlier retirement are possible. The specific nature of the work of seafarers performing their activities in a continuous round-the-clock working cycle provides for the majority of the crew a combination of direct watch duties with a large amount of functions in administration, administrative and general shipboard work, participation in emergency duties, preventive operations, ranging from 9 to 13 hours a day. As a rule, seafarers have two 4-hour watches, although at present there is experience in organizing watch-keeping services on a 6-hour schedule.The survey was conducted in the post-flight period in order to study the influence of fatigue factors on the functional and psycho-physiological state of water transport workers.From the conducted research it follows that fatigue is reversible and the psycho-physiological characteristics are restored after rest. A comprehensive study of fatigue will allow us to adequately assess the level of change in the functional state of the body, preventing somatic reactions in the fatigue phase and develop a set of measures to maintain optimal performance of transport industry specialists.